A Perancangan Sistem Informasi Pengelolaan Data Keluarga Miskin Berbasis Web Dengan Metode Extreme Programming: Indonesia - Baekuni Baekuni; Fitriyanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The village is one of the government agencies responsible for collecting data on the community, especially the poor. The management of the population data information system in Tapos Village still uses a manual system. This can cause some quite troublesome obstacles. there are often problems when searching for data on the poor. With this in mind, the idea arises of how to take advantage of the convenience and cheapness of a mobile/web technology as a means to facilitate data collection on these poor families with a computerized system. The methods used in making the information system for data collection of the poor are the interview method, the observation method and the library study. For software design, the author uses the extreme programming method and the system built is designed with a simple flow and interface design, so that it can be easily used among villages. Where village officials only input population data and data on providing assistance to residents and then the system will store the data, making it easier for officers to manage population data, both upper, middle and poor level residents. With this web-based information system, it is hoped that it can help sub-district officers to record the number of poverty in Tapos-Bogor Village easily, faster and more efficiently so that the results obtained can be accurate, effective and efficient.